2022
DOI: 10.21037/tau-22-327
|View full text |Cite
|
Sign up to set email alerts
|

Development of the prediction model for negative outcomes after primary laparoscopic pyeloplasty in children: a retrospective study of 535 patients

Abstract: Background: Laparoscopic pyeloplasty (LP) has been widely accepted as an effective method to treat ureteropelvic junction obstruction (UPJO) in pediatric patients. Limited studies focused on the relationship between risk factors and negative outcomes. Our study aimed to seek independent risk factors for negative outcomes and construct a prognostic nomogram to assist clinical decision-making and improve outcomes.Methods: A total of 535 patients with UPJO treated with primary LP between January 2016 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Even in these studies, the identified risk factors have been the subject of controversy. [5][6][7][8][9] The objective of this research was to identify the risk factors for adverse outcomes after pediatric pyeloplasty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in these studies, the identified risk factors have been the subject of controversy. [5][6][7][8][9] The objective of this research was to identify the risk factors for adverse outcomes after pediatric pyeloplasty.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few authors have looked for preoperative risk factors that could influence postoperative outcomes. Even in these studies, the identified risk factors have been the subject of controversy 5–9 . The objective of this research was to identify the risk factors for adverse outcomes after pediatric pyeloplasty.…”
Section: Introductionmentioning
confidence: 99%
“…We have read with great interest the contribution done by Li et al , in their study: “ Development of the prediction model for negative outcomes after primary laparoscopic pyeloplasty in children: a retrospective study of 535 patients ” ( 12 ).…”
mentioning
confidence: 99%
“…Secondly, seven surgeons performed operations separately, so bias was unavoidable because these physicians had slightly different preferences and approaches to some details during the surgery. Thirdly, it was a retrospective study ( 12 ). It is a bit contradictory to consider these limitations or weaknesses of the study: on the one hand being a single center, but on the other hand having multiple surgeons.…”
mentioning
confidence: 99%
See 1 more Smart Citation